Birds of Idaho field guide - Tekiela, Stan (Bird identification guides, 2022)
"Get the New Edition of Idaho's Best-Selling Bird Guide. Learn to identify birds in Idaho, and make bird-watching even more enjoyable. With Stan Tekiela's famous field guide, bird identification is simple and informative. There's no need to look through dozens of photos of birds that don't live in your area. This book features 128 species of Idaho birds organized by color for ease of use. Do you see a yellow bird and don't know what it is? Go to the yellow section to find out. Book Features: 128 species: Only Idaho birds -- Simple color guide: See a yellow bird? Go to the yellow section -- Compare feature: Decide between look-alikes -- Stan's Notes: Naturalist tidbits and facts -- Professional photos: Crisp, stunning full-page images. This new edition includes more species, updated photographs and range maps, revised information, and even more of Stan's expert insights. So grab Birds of Idaho Field Guide for your next birding adventure--to help ensure that you positively identify the birds that you see." --Publisher marketing.